Electronic Structure of Mn-Doped ZnO Studied by Using X-ray Absorption Spectroscopy - Thakur, P.; Chae, K. H.; Subramanain, M.; Jayavel, R.; Asokan, K. (KOREAN PHYSICAL SOC, 2008)
Mn-doped ZnO thin films that showed ferromagnetism at room temperature were synthesized with nominal compositions Zn1-x MnxO(x = 0.03, 0.05, 0.07, 0.10 and 0.15) by using a spray pyrolysis technique. High-resolution X-ray diffraction studies suggested that the doped Mn ions occupied Zn sites and that all the samples exhibited a wurtzite hexagonal-like crystal structure similar to that of the parent compound, ZnO. The near-edge X-ray absorption fine structure (NEXAFS) measurements at the 0 K-edge clearly exhibited a pre-edge spectral feature, which evolved with Mn doping, similar to one observed in hole-doped cuprates and manganites. The Mn L-3,L-2-edge NEXAFS spectra exhibited divalent Mn apart from mixed valent Mn3+ / Mn4+ states, which were well supported by Mn K-edge spectra.
Keywords: TRANSITION-METAL COMPOUNDS; MAGNETIC SEMICONDUCTORS; ROOM-TEMPERATURE; THIN-FILMS; FERROMAGNETISM